Sweet wild of mine - Kerr, Laurel (Kerr, Laurel. Wild hearts series, 2019)
In a bid to revitalize his career, bestselling author Magnus Gray has come to Sagebrush Flats to write about the local zoo's latest rescue<U+2015>an orphaned baby polar bear. But Magnus dreads the drama of small towns and is bullishly determined to keep to himself. June Winters is a people person, and delights in welcoming Magnus to Sagebrush Flats, though it seems unlikely she can get the handsome stranger to crack a smile. Then a mishap with an open gate forces Magnus and June to deal with a stampeding flock of fainting goats, an adorable but clingy polar bear cub, a cranky pregnant camel, and two star-crossed honey badgers. Never mind small town drama<U+2015>the lively animals may just convince these two that opposites really do attract...